Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

It is a standard theorem (given in Rudin's Principles of Mathematical Analysis, page 175, and many other places), that if $\{a_{ij}\}$ is a doubly indexed sequence, and

$$\sum_{j=1}^\infty |a_{ij}| = b_i$$and $\sum b_i$ converges, then $$\sum_{j=1}^\infty\sum_{i=1}^\infty a_{ij} = \sum_{i=1}^\infty\sum_{j=1}^\infty a_{ij}$$

Rudin gives a proof relying on standard facts about uniform convergence. However, he also notes that the theorem can be proved directly. Below, I give a "proof" that I have some reservations about.


First, we want to prove that for any integer $M$, $$\sum_{j=1}^\infty\sum_{i=1}^Ma_{ij} = \sum_{i=1}^M \sum_{j=1}^\infty a_{ij}.$$

To prove this, we use the addition rule for series: if $\sum a_i = A$ and $\sum b_i = B$, then $\sum (a_i+b_i) = A + B$. On the right hand side of the equation, we have $M$ sums of the form

$$\sum_{j=1}^\infty a_{ij} = c_i$$

Using the addition rule $M$ times yields

$$\sum_{i=1}^M \sum_{j=1}^\infty a_{ij}= \sum_1^M c_i =\sum_{j=1}^\infty (a_{1j}+ a_{2j}+\cdots+a_{Mj})=\sum_{j=1}^\infty\sum_{i=1}^Ma_{ij} $$

Now, by taking the limit as $M$ goes to infinity above, we have reduced the problem to proving $$\lim_{M \to \infty} \sum_{j=1}^\infty \sum_{i=1}^M a_{ij} = \sum_{j=1}^\infty \sum_{i=1}^\infty a_{ij}.$$

Consider the $M$th partial on the left hand side of the equation. It is


It is not hard to see that by the absolute convergence condition, that this is equal to $a_{1,1}+a_{2,1}+\cdots+a_{M,1}+a_{1,2}+a_{2,2}+\cdots+a_{M,2}+a_{1,3}+a_{2,3}+\cdots+a_{M,3}+\cdots$ (because it is a subsequence), and that this new series is absolutely convergent, so we may rearrange the terms at will. Call this series $S_M$.

The right hand side of the equation is: $ (a_{1,1}+a_{1,2}+a_{1,3}+a_{1,4}+\cdots)+ (a_{2,1}+a_{2,2}+a_{2,3}+a_{2,4}+\cdots)+ (a_{3,1}+a_{3,2}+$ $a_{3,3}+a_{3,4}+\cdots)+\cdots$ ($=\sum b_i$).

Fix $\epsilon>0$. We can find $N$ such that $\epsilon > \sum\limits_{N+1}^{\infty} b_i$. We can also find $J$ such that $\epsilon/N > \sum\limits_{j=J+1}^{\infty} a_{ij}$, for $i\le N$. For any $K$, we can rearrange $S$ to be of the form $(a_{1,1}+a_{1,2}+a_{1,3}+a_{1,4}+\cdots+a_{1,K})+ (a_{2,1}+a_{2,2}+a_{2,3}+a_{2,4}++\cdots+a_{1,K})+ \cdots$ $+(a_{N,1}+a_{N,2}+a_{N,3}+a_{N,4}+\cdots+a_{N,K})+$ [a convergent tail].

Rearrange $S_K$ to be of this form, with $K>J$ and $K$ large enough that the convergent tail has sum less than $\epsilon$. Subtracting this rearrangement from the right hand side gives the result, because the difference can be estimated in terms of $\epsilon$, which we can make as small as we desire. The first $N$ rows each have the first $K$ terms taken off of them, and the remaining sum in each row is less than $N/\epsilon$, so together the $N$ tails left have sum less than $\epsilon$. By the way $N$ was chosen, the remaining rows constitute a tail of the $b_i$ with sum less than $\epsilon$. Finally, the convergent tail that is being subtracted has sum less than $\epsilon$. Using the triangle inequality shows the difference is less than $3\epsilon$, so the partial sums of the left hand side converge to the right hand side, and we are done.

Any comments or suggestions are welcome - I'd like to eventually produce the direct proof Rudin alludes to.

share|cite|improve this question
If you have superior LaTeX knowledge and edit privileges, please feel free to fix my formatting. It runs off the right side near the end, and I can't fix it. – Potato Jan 12 '12 at 6:02
up vote 5 down vote accepted

Your error is here:

and we can take the limit as M goes to infinity on each side

In other words, you are assuming that $$\lim_{M \to \infty} \sum_{j=1}^\infty \sum_{i=1}^M a_{ij} = \sum_{j=1}^\infty \sum_{i=1}^\infty a_{ij}.$$ But this is not in general true.

You've reduced the problem to interchanging a limit and an infinite sum, but taking that last step requires justification, which will have to use the assumptions.

share|cite|improve this answer
Thank you. I will think about this and update the original post. – Potato Jan 12 '12 at 5:05

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.